Pre- and Post-therapy Assessment of Clinical Outcomes and White Matter Integrity in Autism Spectrum Disorder: Pilot Study - Saaybi, Stephanie; AlArab, Natally; Hannoun, Salem; Saade, Maritherese; Tutunji, Rayyan; Zeeni, Carine; Shbarou, Rolla; Hourani, Roula; Boustany, Rose-Mary (Frontiers in Neurology, 2019)
Objective: This pilot study aims to identify white matter (WM) tract abnormalities in Autism Spectrum Disorders (ASD) toddlers and pre-schoolers by Diffusion Tensor Imaging (DTI), and, to correlate imaging findings with clinical improvement after early interventional and Applied Behaviour Analysis (ABA) therapies by Verbal Behaviour Milestones Assessment and Placement Program (VB-MAPP). Methods: DTI scans were performed on 17 ASD toddlers/pre-schoolers and seven age-matched controls. Nine ASD patients had follow-up MRI twelve months following early intervention and ABA therapy. VB-MAPP was assessed and compared at diagnosis, six and twelve months after therapies. Tract-Based Spatial Statistics (TBSS) was used to measure fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial (RD) diffusivity Results: VB-MAPP scores improved at six and twelve months after early intervention and ABA therapy compared to scores at baseline. TBSS analysis showed significant FA decrease and/or RD increase in ASD patients before therapy versus controls in inferior fronto-occipital fasciculi, uncinate fasciculi, left superior fronto-occipital fasciculus, forceps minor, left superior fronto-occipital fasciculus, right superior longitudinal fasciculus, corona radiata bilaterally and left external capsule. A significantly FA increase in 21 tracts and ROIs is reported in post- versus pre-therapy DTI analysis. Conclusion: DTI findings highlighted ASD patient WM abnormalities at diagnosis and confirmed the benefits of twelve months of early intervention and ABA therapy on clinical and neuro imaging outcomes.